1993
DOI: 10.1002/aja.1001960108
|View full text |Cite
|
Sign up to set email alerts
|

Early heart development: Dynamics of endocardial cell sorting suggests a common origin with cardiomyocytes

Abstract: The myocardial and endocardial cell sorting out processes take place primarily between 19 and 29 hr of development in the avian embryo. This occurs in an apparent rostra1 to caudal wave through the heart forming region. During heart development considerable uncertainty exists regarding the processes that regulate cell commitments, progressive aggregation, and sorting out of the different precardiac cell populations. The question addressed in this report is whether endocardial and myocardial cells have a common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 29 publications
(29 reference statements)
3
49
0
1
Order By: Relevance
“…Previous studies of cardiac myocyte development in vitro utilized cells explanted into medium that was supplemented with serum or embryo extract (DeHaan, 1964;Gonzalez-Sanchez and Bader, 1990;Linask and Lash, 1993). Because such supplements are enriched in a variety of growth factors, indications that cardiogenesis can occur in the absence of interacting cells must be cautiously interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of cardiac myocyte development in vitro utilized cells explanted into medium that was supplemented with serum or embryo extract (DeHaan, 1964;Gonzalez-Sanchez and Bader, 1990;Linask and Lash, 1993). Because such supplements are enriched in a variety of growth factors, indications that cardiogenesis can occur in the absence of interacting cells must be cautiously interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, non-muscle cells play important roles in the heart. During embryonic cardiac development, endothelial cells share the same cardiac mesodermal precursors with cardiomyocytes (Linask and Lash 1993). Interaction between endothelial cells and cardiomyocytes in the heart regulates normal heart functions (Narmoneva et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(13) Interestingly, in a study on quail embryos, it was found that EECs and cardiomyocytes initially develop from the same cardiac mesodermal region, although they eventually separate from each other. (14) In fact, in early embryonic development, the EECs are the only endothelial cell subtype present in the primitive spongious heart tube, where they exist alongside the cardiomyocytes, in which, at around this time, the very fi rst contractions begin to appear. (13) The discovery that embryonic EECs release neuregulin, a member of the epidermal growth factor family, supported speculation of an obligatory role for EECs in cardiomyocyte growth and development, especially since it was also (6) shown that the embryonic cardiomyocytes express the neuregulin receptors, ErbB2 and ErbB4.…”
Section: Endothelial Subtypes In the Heartmentioning
confidence: 99%